Pengaruh Kombinasi Media Tanam Terhadap Perkecambahan Benih Mahoni (Swietenia macrophylla) - Imda Natal Kurniati; Astin Elise Mau; Norman Patrick L Bire Riwu Kaho; Pamona Silvia Sinaga (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Mahogany (Swietenia macrophylla) is a broad-leafed forestry plant that can be grown in plantation forests. The conservation status of Mahogany plants is categorized as EN (Endangered) with a declining population trend. Therefore, to overcome these obstacles, efforts are needed to cultivate Mahogany, one of which is the use of planting media. This study aims to determine the effect of the combination of planting media and the most effective treatment on Mahogany seed germination. This study used a Completely Randomized Design (CRD) with 4 treatments, each repeated 3 times, so there were 12 experimental units. Each experiment used 60 Mahogany seeds, so the total seeds needed for all treatments were 720 seeds. The parameters observed included germination power, germination rate, plant height, and number of leaves. The results showed that the combination of planting media in the form of soil, sand, rice husk charcoal, and cow dung had a very significant effect on Mahogany seed germination. P3 treatment (soil 1 kg + sand 1 kg + husk charcoal 1 kg + cow dung 1 kg) provided the best results in terms of germination percentage, plant height, and number of leaves. Furthermore, Treatment P1 (soil 1 kg + sand 1 kg + cow dung 2 kg) provided the best results in terms of germination rate.